Risk factors in the digital space: Children’s Internet and social media use and online victimization (Academic Journal of Internal Affairs, 2023)
Aim: The aim of the study is to provide a comprehensive analysis of children’s Internet usage and their activities in relation to the risk factors and some of the effects of victimisation in the digital world, besides looking at a few of the relevant functional characteristics of social media. By identifying pertinent criminological factors that contribute to harmful behaviours targeting children in the cyber domain, this research contributes understanding of the preventive measures or potential risks associated with online victimisation and the development of digital technologies in safeguarding children online.Methodology: The research mainly reviews and analyses relevant data from academic literature, policy documents, legal sources and statistics in a criminological theoretical context.Findings: The study highlights that children dedicate a substantial amount of time to the digital space, and alongside its advantages, the risk of becoming victims also escalates. Drawing attention to children’s emotional vulnerability and the effects of online abuse is particularly crucial in terms of prevention and intervention. Constant enhancement of regulations and measures, diligent monitoring of international best practices, comprehending and effectively addressing emerging technologies and trends, as well as promoting collaboration among stakeholders, can facilitate a more effective safeguarding of children in cyberspace.Value: The study facilitates a better comprehension of children’s internet usage habits and the risks inherent in them, as well as the processes and circumstances leading to online victimisation, thereby promoting the development of law enforcement and regulatory practices that prioritise effective victim protection and the consideration of children’s rights. Additionally, it aids in the establishment of child protection protocols and collaborations that take into account the aforementioned aspects.
Keywords: online victimisation; internet use; child protection; online child abuse